Caries status in young Colombian children expressed by the ICCMSTM visual/radiographic combined caries staging system (2017)
Objective: To report (1) the caries experience prevalence and mean, and the caries severity and distribution patterns, expressed clinically and combined with radiographs with the conventional and ICCMSTM systems in young children from Bogota, Colombia; (2) the contribution of including radiographs to the clinical caries scoring and (3) in which surfaces the radiograph adds to the clinical caries registration. Material and methods: Six hundred children from kindergartens/schools were enrolled: Cohort A: 2-year (n 1⁄4 200), Cohort B: 4-year (n 1⁄4 200) and Cohort C: 6-year (n 1⁄4 200) olds. Radiographs were taken of the 4- and 6- year olds. Children were examined clinically using the Clinical (C) and Radiographic (R) ICCMSTM-epi Caries Scoring Systems, staging caries lesions (d) as: Initial (Cepi/RA), Moderate (CM/RB) or Extensive (CE/RC). Caries experience including missing (m) and filled (f) surfaces was expressed as follows: clinical conventional (CdMEmfs); clinical ICCMSTM (CdepiMEmfs); combined conventional (C þ RdMEmfs) and combined ICCMSTM (C þ RdepiMEmfs). Results: The prevalence of CdMEmfs was: Cohort A: 32%; Cohort B: 59%; Cohort C: 67.5%, increasing to 73.5%, 99.8% and 100%, respectively, with the C þ R depiMEmfs. The CdMEmfs means doubled when initial caries lesions (Cdepi) and radiographs (R) were included. The d component corresponded to over two-thirds of the caries experience. Findings on the radiographs significantly raised caries experience prevalence and means (p < .02), detecting primarily approximal lesions. Surfaces with highest caries frequency were occlusal/approximal of molar teeth and buccal of upper incisor teeth. Conclusion: Participants’ caries experience was high. The radiographic assessment significantly contributed to caries experience. Molar and upper incisor teeth were most prone to caries.